2007
DOI: 10.1074/jbc.m608214200
|View full text |Cite
|
Sign up to set email alerts
|

Methyltransferase That Modifies Guanine 966 of the 16 S rRNA

Abstract: N2 -Methylguanine 966 is located in the loop of Escherichia coli 16 S rRNA helix 31, forming a part of the P-site tRNA-binding pocket. We found yhhF to be a gene encoding for m 2 G966 specific 16 S rRNA methyltransferase. Disruption of the yhhF gene by kanamycin resistance marker leads to a loss of modification at G966. The modification could be rescued by expression of recombinant protein from the plasmid carrying the yhhF gene. Moreover, purified m 2 G966 methyltransferase, in the presence of S-adenosylometh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 51 publications
1
60
0
Order By: Relevance
“…21 Interestingly, Lesnyak et al recently showed that disruption of the m 2 G966 methyltransferase gene, rsmD, with a kanamycin resistance marker has little effect on the viability or growth rate of E. coli though the knockout strains were slightly less able to compete with wild-type cells when grown in rich medium. 22 Abdi and Fredrick, however, found that any mutation at position 966 resulted in a loss of ribosomal function (see Discussion). 23 Crystal structures of Thermus thermophilus 30S subunits 24 show interactions between the 970 loop and ribosomal proteins S9, S10, and S13.…”
Section: Introductionmentioning
confidence: 89%
“…21 Interestingly, Lesnyak et al recently showed that disruption of the m 2 G966 methyltransferase gene, rsmD, with a kanamycin resistance marker has little effect on the viability or growth rate of E. coli though the knockout strains were slightly less able to compete with wild-type cells when grown in rich medium. 22 Abdi and Fredrick, however, found that any mutation at position 966 resulted in a loss of ribosomal function (see Discussion). 23 Crystal structures of Thermus thermophilus 30S subunits 24 show interactions between the 970 loop and ribosomal proteins S9, S10, and S13.…”
Section: Introductionmentioning
confidence: 89%
“…Here, we have identified and characterized Rv2966c as an RsmD-like methyltransferase from M. tuberculosis by genome data base search, structural, and biochemical analysis. RsmD has m 2 G966 methyltransferase activity for 16 S rRNA in E. coli (14). We have shown that rv2966c can complement rsmD-deleted E. coli cells.…”
mentioning
confidence: 86%
“…In bacteria, nucleotide 966 is predominately a guanosine, but occupied by acp 3 U in archaea (37) and m 1 acp 3 Ψ in eukarya (38). An E. coli strain lacking the G966 modification reveals only a moderate growth disadvantage compared with the wild-type strain (39); however, recent studies have shown that specific mutations at that locus cause mistranslation (P. Cunningham, A. Saraiya, and T. Lamichhane, Wayne State University, personal communication).…”
Section: Effects Of Rrna Methylation On Ribosome Functionmentioning
confidence: 99%